Peripheral and Autonomic Neuropathy Status of Young Patients With Type 1 Diabetes Mellitus at the Time of Transition From Pediatric Care to Adult-Oriented Diabetes Care - Vágvölgyi, Anna; Maróti, Ágnes; Szűcs, Mónika; Póczik, Csongor; Urbán-Pap, Dóra; Baczkó, István; Nemes, Attila; Csajbók, Éva; Sepp, Krisztián; Kempler, Péter; Orosz, Andrea; Várkonyi, Tamás; et al. (Frontiers in Endocrinology, 2021)
The prevalence of neuropathic lesions in young patients with type 1 diabetes mellitus (T1DM) at the time of transition from pediatric care to adult-oriented diabetes care is poorly studied. A comparative study with healthy volunteers to assess the possible neuropathic condition of this special population and to identify the potential early screening needs, has not been performed yet. The results may provide important feedback to pediatric diabetes care and a remarkable baseline reference point for further follow up in adult diabetes care. 29 young patients with T1DM [age: 22.4 ± 2.9 years; HbA1c: 8.5 ± 2.1 %, diabetes duration: 12.2 ± 5.8 years; (mean ± SD)] and 30 healthy volunteers (age: 21.5 ± 1.6 years; HbA1c: 5.3 ± 0.3 %) were involved in the study. Autonomic function was assessed by standard cardiovascular reflex tests. Complex peripheral neuropathic testing was performed by Neurometer®, Neuropad®-test, Tiptherm®, Monofilament® and Rydel-Seiffer tuning fork tests. T1DM patients had significantly higher diastolic blood pressure than controls (80±9 vs. 74 ± 8 mmHg, p < 0.01), but there was no significant difference in systolic blood pressure (127 ± 26 vs. 121 ± 13 mmHg). Cardiovascular reflex tests had not revealed any significant differences between the T1DM patients and controls. No significant differences with Neurometer®, Neuropad®-test and Monofilament® were detected between the two groups. The vibrational sensing on the radius on both sides was significantly impaired in the T1DM group compared to the controls with Rydel-Seiffer tuning fork test (right: 7.5 ± 1.0 vs. 7.9 ± 0.3; left: 7.5 ± 0.9 vs. 7.9 ± 0.3, p < 0.05). The Tiptherm®-test also identified a significant impairment in T1DM patients (11 sensing failures vs. 1, p < 0.001). In addition, the neuropathic complaints were significantly more frequently present in the T1DM patient group than in the controls (9 vs. 0, p < 0.01). In this young T1DM population, cardiovascular autonomic neuropathy and cardiac morphological alterations could not be found. However, Rydel-Seiffer tuning fork and Tiptherm®-tests revealed peripheral sensory neurological impairments in young T1DM patients at the time of their transition to adult diabetes care.